(untitled) (CIPEEX, 2025)
The present work has as object the study on the proof of materiality of the crime of possession of drugs for own use provided in art. 28 of Law n. 11.343/2006, which requires the preparation of a report on the detection of the narcotic substance that shows the nature and quantity of the seized substance, ie, the toxicological report is indispensable for the characterization of the crime in question. The methodology used for the elaboration of this research is the bibliographic, which consists in the exposition of the thoughts of several authors, as well as laws and judges on the subject. According to the judgment of Habeas corpus no 394872-MG, the court’s jurisprudence has established the orientation on the sense that the toxicological report is essential for proving the materiality of the offence, that is, even if there is a final judgment of the conviction for the commission of the crime of possession of drugs for own consumption and such sentence is dispensable for the recognition of the serious offence, for there is really the recognition of the material delict is of paramount importance to the preparation of the preliminary report, it is important to emphasize that without it is not feasible the crime in flagrante. Concluding the definitive toxicological report is essential for the configuration of the crime of illicit trafficking in narcotics, under penalty of having the materiality of the offence uncertain and therefore, to grant the accused’s acquittal.